2023
DOI: 10.3389/fspor.2022.1072154
|View full text |Cite|
|
Sign up to set email alerts
|

Look to the stars—Is there anything that public health and rehabilitation can learn from elite sports?

Abstract: Millet GP and Chamari K (2023) Look to the stars-Is there anything that public health and rehabilitation can learn from elite sports? Front. Sports Act. Living 4:1072154.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…Finally, integrative research in exercise should be combined with exercise medicine to further our understanding of the immense potential of exercise-based interventions to prevent and treat many chronic diseases in the general population ( 821 ), along with the use of training for injury rehabilitation in physical therapy. A better understanding in the athletic setting thus could and should inform interventions in the general population and in patients ( 822 ). For example, studies of resilience and motivation might also help to design approaches to facilitate and improve adherence and compliance to exercise training ( 823 825 ).…”
Section: Summary Conclusion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, integrative research in exercise should be combined with exercise medicine to further our understanding of the immense potential of exercise-based interventions to prevent and treat many chronic diseases in the general population ( 821 ), along with the use of training for injury rehabilitation in physical therapy. A better understanding in the athletic setting thus could and should inform interventions in the general population and in patients ( 822 ). For example, studies of resilience and motivation might also help to design approaches to facilitate and improve adherence and compliance to exercise training ( 823 825 ).…”
Section: Summary Conclusion and Perspectivesmentioning
confidence: 99%
“…Insights into exercise physiology are leveraged in disease diagnostic, prevention, treatment, and rehabilitation, e.g., the use of blood pressure measurements during exercise (exercise hypertension) to reveal undiagnosed or masked hypertension and predict cardiovascular disease risks ( 828 , 829 ). Many more areas exist in which concepts derived from elite sports will benefit non-athletes and patients ( 822 ). In this context, exercise sociology could contribute to overcome existing individual and societal challenges ( 830 ).…”
Section: Summary Conclusion and Perspectivesmentioning
confidence: 99%
“…Similarly, VO 2 max thus represents an exquisite example for a mainstay tool initially developed for elite sport research that has subsequently shown a massive clinical potential. 37…”
Section: Practical Applications and Conclusionmentioning
confidence: 99%